Functional properties of amaranth, quinoa and chia proteins and the biological activities of their hydrolyzates - López, Débora Natalia (2019)
Amaranth, quinoa and chia are non-conventional sources of proteins whose interest has increased in recent years due to their excellent nutritional value. Vegetable proteins can be used as food ingredients to replace animal proteins in human diet. The present article provides a comprehensive analysis of amaranth, quinoa and chia proteins and focuses on their solubility, superficial, gelling and textural properties as well as on the biological activities of enzymatic hydrolyzates.